2019
DOI: 10.1039/c9sc04096j
|View full text |Cite
|
Sign up to set email alerts
|

The butterfly effect in bisfluorenylidene-based dihydroacenes: aggregation induced emission and spin switching

Abstract: Difluorenylidene dihydroanthracene with a butterfly-like structure exhibits both aggregation induced emission (AIE) and thermally activated ground-state spin switching properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 51 publications
3
45
0
1
Order By: Relevance
“…The coordination sphere of the boron atoms is close to trigonalplanar (4a S B1-4 each 359.48 8; 4b S B = 359.3, 359.78 8); however, they are significantly bent out of the central B 2 C 4 ring plane by 44.0-45.38 8.S uch bent, butterfly-type structures were also reported for related isoelectronic,quinoidal anthracenes with carbon-based substituents in 9,10-positions. [27] Thes trong electronic impact of the cAAC R ligands becomes evident by inspection of the exocyclic BÀC cAAC bonds of 4a/4b (1.506-(7)-1.531(2) ). These are notably shortened as compared to radical cations 3a/3b with typical dative single bonds (1.632-(5), 1.638(5) ), which implies substantial delocalization of the two unpaired electrons in 4a/4b and BÀC cAAC multiple bond character.…”
Section: Resultsmentioning
confidence: 99%
“…The coordination sphere of the boron atoms is close to trigonalplanar (4a S B1-4 each 359.48 8; 4b S B = 359.3, 359.78 8); however, they are significantly bent out of the central B 2 C 4 ring plane by 44.0-45.38 8.S uch bent, butterfly-type structures were also reported for related isoelectronic,quinoidal anthracenes with carbon-based substituents in 9,10-positions. [27] Thes trong electronic impact of the cAAC R ligands becomes evident by inspection of the exocyclic BÀC cAAC bonds of 4a/4b (1.506-(7)-1.531(2) ). These are notably shortened as compared to radical cations 3a/3b with typical dative single bonds (1.632-(5), 1.638(5) ), which implies substantial delocalization of the two unpaired electrons in 4a/4b and BÀC cAAC multiple bond character.…”
Section: Resultsmentioning
confidence: 99%
“…[171] Previously, it had been assumed that such motions as twisting, stretching, torsion, wagging, and rocking of AIEgens in solution causing nonradiative decay would effectively be shut off or dramatically attenuated in the solid state. [172][173][174][175][176] However, there is of course some motion and disorder that is always expected for any material above 0 K (the third law of thermodynamics). The significance of the remaining vibrational motions of TPE in the solid state was proven by the increase of PL of crystalline TPE analogs with decreasing temperature by temperature-dependent fluorescence measurements.…”
Section: Dynamic Aggregatesmentioning
confidence: 99%
“…[6,7] Diverse SLE luminogens with sterically congested structures, such as butterflylike or propeller-like shapes, have been designed to reduce intermolecular stacking interactions. [9,[22][23][24] In these cases,t he effect of intramolecular interactions on the photophysical properties of the material could gain importance and should also be considered. Styrylarenes are aw ell-known family of compounds, [25][26][27][28][29][30] but only af ew studies on their solid-state photophysical properties have been reported, to date.…”
Section: Introductionmentioning
confidence: 99%